Mathematics lecturer’s values and their choice of technology for their instruction in one university in Malaysia - Ponniah, Logendra Stanley (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
With the current rise in popularity in using technology to enhance the students’ learning experience, mathematics lecturers are pressured to incorporate technology in their instructional design. The situation becomes problematic when many of these lecturers’ learning experiences have a limited exposure to teaching and learning technology. To compound this decision making further, technology tools offered to lecturers’ are numerous in terms of functions and forms. This study focuses on how mathematics lecturers’ in one university in Malaysia decide on what technology to use and what are the factors that are involved in their decision-making. This study presents the narrative of five mid-career mathematics lecturers and how they meaningfully selected, used technology and incorporated technology into their instructional designs. The evidence in this study suggests that lecturers’ decision on what technology they use in their instructional design tend to be in an ad-hoc manner and above all it is their belief in mathematics that appears to predict their utilization of technology. The finding of this study is valuable in guiding organizations and individuals who are interested to incorporate technology in designing mathematics instruction.